Normative Approach to Law and Economics in Developing Countries: Challenges in Establishing Efficient and Just Market Regulations - Meitasari, Intan; Suratno, Suratno; Yuniwati, Yuniwati (Journal of Law and Economics, 2025)
Market regulation in developing economies confronts a fundamental dilemma: how to achieve allocative efficiency without sacrificing distributive justice. Drawing on normative–empirical analysis of legal materials, policy frameworks, and comparative data from Indonesia, India, and Brazil, the research exposes persistent friction between growth-maximizing policies and principles of equity, legal certainty, and institutional legitimacy. Regulatory systems across these jurisdictions consistently favor efficiency metrics while sidelining distributional consequences—a pattern that widens socioeconomic gaps and weakens public confidence in state institutions. Countries with stronger legal infrastructures and mature normative traditions demonstrate greater capacity to embed justice considerations within economic governance. The study proposes a law–economics model where legal normativity operates not as ancillary to economic logic but as foundational to regulatory design, anchoring policy in fairness, predictability, and collective welfare. Theoretically, the work recasts law's dual role as both boundary and catalyst in economic systems. Practically, it outlines strategies for enhancing regulatory clarity, institutional responsibility, and policy credibility in developing settings—charting routes to prosperity that do not undermine social solidarity.